Communicating Strategic Cloud Value: Bridging the Gap between IT and Business Leadership - Shamkura, Srinivas (International Journal of Computing and Engineering, 2025)
This article examines the critical challenge faced by technology leaders in effectively communicating the strategic value of cloud computing to business executives. While cloud technologies offer transformative benefits beyond cost reduction such as enhanced agility, accelerated innovation, and improved resilience these advantages often remain poorly articulated in terms that resonate with C-suite decision-makers. Through analysis of communication practices and interdepartmental dynamics, effective frameworks, language patterns, and evidence types that successfully bridge the technical-business divide are identified. The article findings provide practical guidance for technology leaders seeking to secure executive buy-in for strategic cloud initiatives by aligning technology capabilities with priority business outcomes including accelerated time-to-market, revenue diversification, customer experience enhancement, operational resilience, and competitive differentiation.